Analisis Pengaruh JUB, E-Money dan BI7DRR Terhadap Inflasi Di Indonesia Pada Masa Pandemic Covid-19 - Nela Permatasari Lubis (JOURNAL ECONOMICS AND STRATEGY, 2022)
Inflation is one of the monetary phenomena that can disrupt the stability of a country's economy if it is not controlled properly. The purpose of the study was to determine the effect of JUB, E-Money and BI7DRR simultaneously and partially on inflation in Indonesia during the Covid-19 pandemic. This type of research is an associative type of research using multiple linear regression analysis techniques. The results show that (1) the money supply partially has a significant effect on inflation in Indonesia, (2) the e-money partially has no significant effect on inflation in Indonesia, (3) the BI7DRR partially has a significant effect on inflation in Indonesia (4) Money Supply, E-Money, and BI7DRR simultaneously circulated with a significant effect on Inflation in Indonesia